Bone Morphogenetic Protein-4 Inhibits Corticotroph Tumor Cells: Involvement in the Retinoic Acid Inhibitory Action - Giacomini, Damiana Paula (2006)
The molecular mechanisms governing the pathogenesis of ACTH-secreting pituitary adenomas are still obscure. Furthermore, the pharmacological treatment of these tumors is limited. In this study, we report that bone morphogenetic protein-4 (BMP-4) is expressed in the corticotrophs of human normal adenohypophysis and its expression is reduced in corticotrophinomas obtained from Cushing's patients compared with the normal pituitary. BMP-4 treatment of AtT-20 mouse corticotrophinoma cells has an inhibitory effect on ACTH secretion and cell proliferation. AtT-20 cells stably transfected with a dominant-negative form of the BMP-4 signal cotransducer Smad-4 or the BMP-4 inhibitor noggin have increased tumorigenicity in nude mice, showing that BMP-4 has an inhibitory role on corticotroph tumorigenesis in vivo. Because the activation of the retinoic acid receptor has an inhibitory action on Cushing's disease progression, we analyzed the putative interaction of these two pathways. Indeed, retinoic acid induces both BMP-4 transcription and expression and its antiproliferative action is blocked in Smad-4dn- and noggin-transfected Att-20 cells that do not respond to BMP-4. Therefore, retinoic acid induces BMP-4, which participates in the antiproliferative effects of retinoic acid. This new mechanism is a potential target for therapeutic approaches for Cushing's disease.